4-Hydroxy-N,N-diisopropyltryptammonium hydrofumarate - Marilyn Naeem; Andrew R. Chadeayne; James A. Golen; David R. Manke (IUCrData)
The solid-state structure of the title salt, C16H25N2O+·C4H3O4− {systematic name: [2-(4-hydroxy-1H-indol-3-yl)ethyl]bis(propan-2-yl)azanium (2E)-3-carboxyprop-2-enoate}, is reported. In the extended structure, the hydrofumarate anions form linear chains propagating in the [100] direction through O—H...O hydrogen bonds that combine with the tryptammonium cations to generate a three-dimensional network linked by O—H...O and N—H...O hydrogen bonds.